Temperatures in two boreholes at Flüela Pass, Eastern Swiss Alps: the effect of snow redistribution on permafrost distribution patterns in high mountain areas - Martina Luetschg; Veronika Stoeckli; Michael Lehning; Wilfried Haeberli; Walter Ammann (Permafrost and Periglacial Processes)
Snow cover distribution strongly affects soil temperatures and, thus, plays a decisive role in determining permafrost distribution patterns. Redistribution of snow by avalanches and snow drift significantly affects the snow‐melt pattern and soil temperatures in steep avalanche slopes of high mountain areas. At Flüela Pass, 2380 m a.s.l., eastern Swiss Alps, the presence and origin of permafrost that occurs at the base of an avalanche‐affected slope below the regional lower limit of discontinuous permafrost was studied by field investigations and numerical simulations. Local permafrost distribution has been determined in former studies by applying geophysical methods and this was confirmed with two boreholes drilled at the slope base and in the avalanche starting zone. Temperature measurements confirm the presence of a 10 m thick permafrost body with temperatures close to the freezing point at the slope base. Numerical simulations of different snow‐cover scenarios for 2002/03 demonstrate the particular effect on soil temperatures of high snow drift accompanying intense snow falls in early winter, controlling the duration of constant zero temperatures at the base of the snow pack at the beginning of the snow period. Copyright © 2004 John Wiley & Sons, Ltd.